Emergency nurses' knowledge about ventilator-associated pneumonia. (January 2020) - Rafiei, Hossein; Rahimi, Sara; Shafaei, Mahya; Ommatmohammadi, Mirmostafa
Highlights: Study about emergency nurses about prevention of ventilator-associated pneumonia is very limited. Results of present study revealed that emergency nurses have an inadequate knowledge about the prevention of ventilator-associated pneumonia. Participating in training course on caring of mechanically ventilated patients and being familiar with the international guidelines of prevention of ventilator-associated pneumonia impact nurses' knowledge positively. It is necessary to improve the knowledge of the emergency nurses about prevention of ventilator-associated pneumonia. Abstract: Introduction: Given the increasing number of patients requiring mechanical ventilation in emergency departments in recent years, prevention of ventilator-associated pneumonia is very important. Nurses play a significant role in prevention of ventilator-associated pneumonia. This study aimed to determine the emergency nurses knowledge about prevention of ventilator-associated pneumonia. Methods: The present descriptive study was conducted in Iran, from July to October 2018. All the nurses with at least a bachelor degree, who are working in two emergency departments of two teaching hospitals, were asked to participate in this study. The "knowledge about ventilator-associated pneumonia" questionnaire consisting of 9 items was used to assess the knowledge of nurses. The results were analyzed using SPSS-16. Results: In total, 53 nurses participated in this study. The mean score of correct answers of nurses to these 9 items was 4.4 ± 1.6. Nurses give the most correct answer to the item about patient's position on the bed so as to reduce the risk of pneumonia with a correct answer of 72.9%. The least correct answer was also given to the item about how humidifier was changed with a correct answer of 1.9%. None of the nurses participating in the study were able to answer all the items correctly. The mean score of knowledge of nurses who had participated in workshops about taking care of patients on mechanical ventilation was significantly higher than those who had not participated in such workshops (4.8 vs. 3.8) (p = 0.045). The mean score of knowledge in nurses who were familiar with the international guidelines for ventilator-associated pneumonia prevention was significantly higher than those who were not familiar with such guidelines (5.1 vs. 4.1) (p = 0.045). Conclusion: Emergency nurses participated in this study had inadequate knowledge about the prevention of ventilator-associated pneumonia. Nurse's knowledge affected by participation in related workshop and familiarity with ventilator-associated pneumonia guidelines. Considering the importance of this issue, it is necessary to improve the knowledge of the emergency nurses in this matter by holding training courses.